Mortality Benefit of Rivaroxaban Plus Aspirin in Patients With Chronic Coronary or Peripheral Artery Disease - Eikelboom, John W; Bhatt, Deepak L; Fox, Keith A A; Bosch, Jacqueline; Connolly, Stuart J; Anand, Sonia S; Avezum, Alvaro; Berkowitz, Scott D; Branch, Kelley R H; Dagenais, Gilles R; Félix, Camilo; Guzik, Tomasz J; et al. (Journal of the American College of Cardiology, 2021)
The combination of 2.5 mg rivaroxaban twice daily and 100 mg aspirin once daily compared with 100 mg aspirin once daily reduces major adverse cardiovascular (CV) events in patients with chronic coronary artery disease (CAD) or peripheral artery disease (PAD).BACKGROUNDThe combination of 2.5 mg rivaroxaban twice daily and 100 mg aspirin once daily compared with 100 mg aspirin once daily reduces major adverse cardiovascular (CV) events in patients with chronic coronary artery disease (CAD) or peripheral artery disease (PAD).The aim of this work was to report the effects of the combination on overall and cause-specific mortality.OBJECTIVESThe aim of this work was to report the effects of the combination on overall and cause-specific mortality.The COMPASS trial enrolled 27,395 patients of whom 18,278 were randomized to the combination (n = 9,152) or aspirin alone (n = 9,126). Deaths were adjudicated by a committee blinded to treatment allocation. Previously identified high-risk baseline features were polyvascular disease, chronic kidney disease, mild or moderate heart failure, and diabetes.METHODSThe COMPASS trial enrolled 27,395 patients of whom 18,278 were randomized to the combination (n = 9,152) or aspirin alone (n = 9,126). Deaths were adjudicated by a committee blinded to treatment allocation. Previously identified high-risk baseline features were polyvascular disease, chronic kidney disease, mild or moderate heart failure, and diabetes.During a median of 23 months of follow-up (maximum 47 months), 313 patients (3.4%) allocated to the combination and 378 patients (4.1%) allocated to aspirin alone died (hazard ratio [HR]: 0.82; 95% confidence interval [CI]: 0.71-0.96; P = 0.01). Compared with aspirin, the combination reduced CV death (160 [1.7%] vs 203 [2.2%]; HR: 0.78; 95% CI: 0.64-0.96; P = 0.02) but not non-CV death. There were fewer deaths following MI, stroke, and CV procedures, as well as fewer sudden cardiac, other, and unknown causes of CV deaths and coronary heart disease deaths. Patients with 0, 1, 2, and 3 or 4 high-risk features at baseline had 4.2, 4.8, 25.0, and 53.9 fewer deaths, respectively, per 1000 patients treated for 30 months.RESULTSDuring a median of 23 months of follow-up (maximum 47 months), 313 patients (3.4%) allocated to the combination and 378 patients (4.1%) allocated to aspirin alone died (hazard ratio [HR]: 0.82; 95% confidence interval [CI]: 0.71-0.96; P = 0.01). Compared with aspirin, the combination reduced CV death (160 [1.7%] vs 203 [2.2%]; HR: 0.78; 95% CI: 0.64-0.96; P = 0.02) but not non-CV death. There were fewer deaths following MI, stroke, and CV procedures, as well as fewer sudden cardiac, other, and unknown causes of CV deaths and coronary heart disease deaths. Patients with 0, 1, 2, and 3 or 4 high-risk features at baseline had 4.2, 4.8, 25.0, and 53.9 fewer deaths, respectively, per 1000 patients treated for 30 months.The combination of rivaroxaban and aspirin compared with aspirin reduced overall and CV mortality with consistent reductions in cause specific CV mortality in patients with chronic CAD or PAD. The absolute mortality benefits are greater with increasing baseline risk. (Cardiovascular Outcomes for People Using Anticoagulant Strategies [COMPASS]; NCT01776424).CONCLUSIONSThe combination of rivaroxaban and aspirin compared with aspirin reduced overall and CV mortality with consistent reductions in cause specific CV mortality in patients with chronic CAD or PAD. The absolute mortality benefits are greater with increasing baseline risk. (Cardiovascular Outcomes for People Using Anticoagulant Strategies [COMPASS]; NCT01776424).